Analysis of the protection of the American diplomatic missions involving in the internal conflicts since the 2000s from the legal perspective - Beļčikova, Darija (Riga Graduate School of Law, 2020)
Different attacks on the diplomatic staff were documented since the 19th century and it will decrease global stability and damage the relations between countries. Concerning the protection of American diplomatic missions, it became a more important issue for the United States since the 20th century, while a country faced with illegal actions such as assassinations of the state representatives organized directly or indirectly by different groups of people, who do not support American ideology, policy and interests. Moreover, the physical protection of the embassy was a crucial way to protect the diplomatic staff against violence. Still, in reality, it was difficult to achieve due to the unpreparedness and unwillingness of the receiving State to secure the host representatives, especially in armed conflict while needed. Nevertheless, the concept of protection is regulated by international law and decides how to impose legislation to all these events and constitute its breach. Within this paper, the main issue will be discussed: how the Anti-Americanism affects on the security of diplomatic representations and staff abroad since 2000, how is international law applicable to diplomatic missions protection and how the United States responds to threats to the American diplomatic representations in the 21st century
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Diplomatic law